Management of Secondary Osteoarthritis with Proximal Femoral Deformity due to Previous Coxitis Hip: A Case Report - Renaldi, Rizal; Afrian, Jifaldi; Chilmi, Mohammad Zaim (The Hip and Knee Journal, 2023)
Most proximal femoral deformities encountered during hip arthroplasty are secondary to degenerative processes, previous osteotomy, or fracture and could be a challenged for surgeons. Femoral deformity may be angular, rotational, or one of bone diameter or length. Fully understanding the anatomy of the deformity is the first element in deciding how to best treat the deformity during Total Hip Arthroplasty (THA). Female 31 years old complaint of pain on her left hip with restricted motion, with a leg length discrepancy (LLD) of 2 cm and a history of operation due to left hip infection when she was a baby. THA was performed with carefully evaluating the abductor muscle to maintain hip stability. Postoperatively the patient has an equal leg length, with less pain on the hip, a good ROM, and able to walk dependently using a cane. Slight tightness on the abductor and adductor muscle was noted postoperatively and the patient undergone physiotherapy. Multiple important factor must be considered before considering THA in patients with proximal femoral deformity, including abductor function, osseous anatomy, hip stability and LLD. One must be careful of correction of LLD greater than 3 cm because possible effect on abductor strength, hip stability and sciatic nerve function. In this case, we demonstrated that a successful THA can be achieved despite altered anatomy due to secondary developmental changes. In the setting of sufficient abductor strength and bony stock amenable to implant fixation, THA is a viable option for management and careful preoperative planning helps predict prosthesis requirements and technical challenges.